ANALISIS SUPPLY BAGI STANDAR MANAJEMEN PENGEMBANGAN DI KAWASAN EKOWISATA RAJA AMPAT (*) - Wiriadi Sutrisno (UNIVERSITAS INDRAPRASTA PGRI, 2015)
Tourism industry is one of the economic sub-sector that is able to contribute Government revenue, after Oil and Gas (MIGAS) export. Raja Ampat is a Tourism Destination Region (DTW) featured by this time, which is rich with coral reefs. However, the wealth of biodiversity has made itself high level of threat as well. It can be seen from damage to coral reefs and forests, due to fishing activities which are not environmental friendly such as bombs, cyanide and roots bore. Phenomenon in the world of tourism is showing a favorable prospects of the business side. This industry market conditions indicate a